Testing whether Mixed Lineage Kinase-3 (MLK-3) opposes Pathological Cardiac Hypertrophy through inhibition of the Transcription Factor, Nuclear Factor of Activated T cells (NFAT) in the Cardiac Myocytes - Raymond, Loveth. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023-03.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Robert Blanton.; Keywords: Pharmacology, Pharmacology, and Pharmaceutical sciences.